Colorectal Cancer Screening in Average Risk Populations: Evidence Summary. (14th August 2016) - Tinmouth, Jill; Vella, Emily T.; Baxter, Nancy N.; Dubé, Catherine; Gould, Michael; Hey, Amanda; Ismaila, Nofisat; McCurdy, Bronwen R.; Paszat, Lawrence
Abstract : Introduction . The objectives of this systematic review were to evaluate the evidence for different CRC screening tests and to determine the most appropriate ages of initiation and cessation for CRC screening and the most appropriate screening intervals for selected CRC screening tests in people at average risk for CRC. Methods . Electronic databases were searched for studies that addressed the research objectives. Meta-analyses were conducted with clinically homogenous trials. A working group reviewed the evidence to develop conclusions. Results . Thirty RCTs and 29 observational studies were included. Flexible sigmoidoscopy (FS) prevented CRC and led to the largest reduction in CRC mortality with a smaller but significant reduction in CRC mortality with the use of guaiac fecal occult blood tests (gFOBTs). There was insufficient or low quality evidence to support the use of other screening tests, including colonoscopy, as well as changing the ages of initiation and cessation for CRC screening with gFOBTs in Ontario. Either annual or biennial screening using gFOBT reduces CRC-related mortality. Conclusion . The evidentiary base supports the use of FS or FOBT (either annual or biennial) to screen patients at average risk for CRC. This work will guide the development of the provincial CRC screening program.